Class 6 Maths: Framing Algebraic Expressions - Simplification
Simplify the following algebraic expressions. Click to reveal hints and answers!
Puzzle 1
Simplify 12x - (6x + 8x)
Hint: Combine like terms inside the brackets first.
Answer: 12x - (6x + 8x) = 12x - 14x = -2x
Puzzle 2
Simplify 5x + (3x - 4x)
Hint: Combine like terms inside the brackets first.
Answer: 5x + (3x - 4x) = 5x - x = 4x
Puzzle 3
Simplify 3a + [2b - (a + b)]
Hint: Start by solving the expression inside the parentheses first.
Answer: 3a + [2b - (a + b)] = 3a + 2b - a - b = 2a + b
Puzzle 4
Simplify 4x + [2(x + 3) - 3x]
Hint: First expand the brackets, then combine like terms.
Answer: 4x + [2(x + 3) - 3x] = 4x + [2x + 6 - 3x] = 4x + (-x + 6) = 3x + 6
Puzzle 5
Simplify 7y - (3y + 4z) + 2z
Hint: Combine like terms and keep the variables separate.
Answer: 7y - (3y + 4z) + 2z = 7y - 3y - 4z + 2z = 4y - 2z
Puzzle 6
Simplify 6a - [3a + (2a - 5)]
Hint: Simplify the innermost bracket first.
Answer: 6a - [3a + (2a - 5)] = 6a - [3a + 2a - 5] = 6a - 5a + 5 = a + 5
Puzzle 7
Simplify 4x - (3x - 2y) + 6y
Hint: Distribute the negative sign and then combine like terms.
Answer: 4x - (3x - 2y) + 6y = 4x - 3x + 2y + 6y = x + 8y
Puzzle 8
Simplify 5a + [3a - (a + 2)]
Hint: Simplify the expression inside the brackets first.
Answer: 5a + [3a - (a + 2)] = 5a + [3a - a - 2] = 5a + 2a - 2 = 7a - 2
Puzzle 9
Simplify 3x + (2x - 4) - [x + (x - 2)]
Hint: Start by simplifying the innermost brackets first, then proceed outward.
Answer: 3x + (2x - 4) - [x + (x - 2)] = 3x + 2x - 4 - [x + x - 2] = 3x + 2x - 4 - 2x + 2 = 3x - 2
Puzzle 10
Simplify 2x - [5x - (3x + 4)]
Hint: Solve the innermost brackets first, then continue simplifying.
Answer: 2x - [5x - (3x + 4)] = 2x - [5x - 3x - 4] = 2x - [2x - 4] = 2x - 2x + 4 = 4